Culturally Responsive Clay Modeling Interventions: Improving Fine Motor Skills and Cultural Connection in Slow Learner Children - Karsini, Karsini; Suparno, Suparno (Journal of Innovation and Research in Primary Education, 2025)
Fine motor skills development presents significant challenges for slow learners in early childhood education. This study investigated the effectiveness of local wisdom-based play methods using geometric clay modeling activities to enhance fine motor skills among slow learner children in kindergarten settings. A collaborative classroom action research design following the Kemmis and McTaggart model was implemented across three cycles at State Kindergarten 1, Long Mesangat District. Five male participants aged 5-6 years, identified as slow learners with fine motor difficulties, engaged in structured clay modeling activities incorporating traditional geometric patterns. Data collection utilized systematic observations with validated checklists assessing five domains: hand dexterity, eye-hand coordination, muscle strength, cultural integration, and motivation levels. Performance was evaluated using four developmental categories from "Not Yet Developed" to "Very Well Developed." Substantial improvements occurred across all intervention cycles. Baseline assessment revealed 80% of participants classified as "Not Yet Developed" and 20% as "Beginning to Develop." Following three intervention cycles, final outcomes showed 60% achieving "Very Well Developed" status and 40% reaching "Developing as Expected" levels. No participants remained in lower developmental categories by study completion. Teacher performance also improved from predominantly "Fair" ratings to 75% "Excellent" evaluations. Local wisdom-based clay modeling activities effectively enhanced fine motor skills in slow learners through culturally responsive, hands-on learning approaches. The progressive improvement pattern demonstrates the value of systematic, repeated interventions utilizing traditional materials and techniques. Results support the integration of culturally relevant practices in special education programming, providing evidence for effective inclusive education strategies that honor both individual learning needs and cultural heritage.